Mesalamine-induced myopericarditis in children: a case report and a short revision of the literature - Lecis, Marco; Stefanelli, Francesca; Montanari, Federica; Di Biase, Anna Rita; Lucaccioni, Laura; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2024)
Mesalamine has a central role in the treatment of inflammatory bowel disease (IBD). Myocarditis and/or pericarditis are rare and severe side effects of mesalamine-containing drugs. We describe the case of a 14 years old boy, developing myopericarditis two weeks after starting mesalamine treatment for ulcerative colitis (UC). The adverse effect had a massive impact on the left ventricular function and required immediate intervention. Once identified as possible causative agent, mesalamine was discontinued with subsequent improvement of the clinical symptoms and laboratory findings. No recurrency nor sequelae were detected at the cardiological follow up. Mesalamine is a widely used drug for pediatric IBD treatment, although its effect on heart tissues is a rare but potentially fatal adverse reaction. At the time of presentation, in April 2021, 10 pediatric cases were reported in literature (2 children and 8 adolescents). Of them, 60% were treated with mesalamine for UC and 40% for Chron’s disease (CD). Chest pain and fever were the most common symptoms at presentation (100% and 50% respectively), cough and fatigue were less represented. None of the patients developed sequelae at follow up. In patients treated with mesalamine early recognition of side effects, drug discontinuation and accurate therapy are crucial to prevent progression of the inflammation and to avoid adverse cardiovascular outcomes.